Implementasi Video Animasi Untuk Perkembangan Bahasa Anak Usia Dini - Anggraeni, Denok Dwi; Ummah, Lina Wardatul (Institut Agama Islam Negeri Ponorogo, 2024)
The objectives of this study: first, to determine the implementation of animated videos for the development of early childhood language at PAUD Bina Rahima; second, to determine the inhibiting and supporting factors for the implementation of animated videos for the development of early childhood language at PAUD Bina Rahima; third, to determine the impact of the implementation of animated videos for the development of early childhood language at PAUD Bina Rahima. This study uses a descriptive qualitative approach. Data collection techniques through interviews with the principal, teachers, PAUD Bina Rahima, as well as observation and documentation. Meanwhile, checking the validity of the data is done through extension of participation, and triangulation. The results of the study show that: first, the implementation of animated videos for the development of early childhood language at PAUD Bina Rahima, is started with the opening, then the teacher carries out the core activities of the learning material using animated video media, and finally provides an evaluation after the learning is complete; second, the inhibiting factor for the implementation of animated videos is that some children are less disciplined and difficult to control. While the supporting factor is the availability of adequate facilities; third, the impact of the implementation of animated videos, is that children are able to make two simple sentences, and children are able to interact with others.